The Application of MIPVU in News Text: Comparison between Male and Female Writings - Noor Amalia Utami (Universitas Brawijaya, 2019)
The study of metaphor has extended from conceptual theory to metaphor identification. The proposed procedure known as MIPVU has been used in many works to determine the metaphorical words. There are some modifications on the use of MIPVU such as what Pitcher (2013) and Wu (2017) did. This research will present qualitative result as an illustration of the identification and quantitative result as measurement of the findings. Both results show that male’s writing uses indirect metaphor and direct metaphor. The use of direct metaphor also cause the use of metaphor indicator. Meanwhile, the only metaphor type found in female’s writing is indirect metaphor. The metaphors found in female’s writing spread on noun, verb, adjective and preposition. While, metaphors male’s writing in highly identified in verb.